Severe Cutaneous Adverse Drug Reaction - Damayanti Damayanti; Sylvia Anggraeni; Cita Rosita SP; Marsudi Hutomo; Hari Sukanto (Department of Dermatology and Venereology, Faculty of Medicine, Universitas Airlangga, 2017)
Background: Cutaneous adverse drug eruption (CADR) are frequently found. A systematic review showed, the incidence of severe CADR (SCADR) ranging from 0-8%. Few studies have assessed the severe form of CADR, which has high mortality rate. The epidemiological study was needed to show the profile of SCADR, especially in the setting of general hospital. Purpose: To evaluate clinical and epidemiological profile of SCADR in Dermatology and Venereology Ward Dr. Soetomo Hospital Surabaya. Methods: All SCADR patients in the period of January 2015-January 2016 was evaluated clinically and epidemiologically. Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), acute generalized exanthematous pustulosis (AGEP), and drug reaction with eosinophilia and systemic reaction (DRESS) cases were included in the study. Results: There were 14 patients in this study, consist of 10 SJS cases (71.4%), 2 TEN patients, and 2 AGEP patients. The highest frequency of age group was 25-29 years old (57.1%). Man to woman ratio was 3:4. The most common offending drug was paracetamol (50%), followed by amoxicillin (28.6%). Antibiotic was the highest frequent offending drug-group (64.3%), followed by antipiretics (50%). In this study, all patients got systemic corticosteroid and the mortality was 0%. Conclusion: The most common type of SCADR was SJS. The most common offending drug was paracetamol, and antibiotic was the highest frequent offending drug-group. Systemic corticosteroid therapy showed good result in severe CADR management.